Value-added application of cattle manure bottom ash for phosphorus recovery from water and replenishment in soil - Lee, Jae In; Jadamba, Chuluuntsetseg; Yoo, Soo Cheul; Lee, Chang Gu; Park, Seong Jik (Journal of Environmental Management, 2023)
This study addresses ways to circulate the flow of phosphorus (P) from water to soil to improve water quality and provide a sustainable supply of P into soil. Here, bottom ash (BA_CCM), the byproduct of the combustion of cattle manure, which is performed for obtaining energy, was used to remove P in wastewater. Next, the P-captured BA_CCM was used as P fertilizer for rice growth. BA_CCM was primarily composed of Ca (49.4%), C (24.0%), and P (9.9%), and the crystalline phases of Ca were calcium carbonate (CaCO3) and hydroxyapatite (Ca5(PO4)3OH). The mechanism of P removal by BA_CCM involves the formation of hydroxyapatite by reacting Ca2+ with PO43−. A reaction time of 3 h was required to achieve P adsorption to BA_CCM, and the maximum P adsorption capacity of BA_CCM was 45.46 mg/g. The increase in solution pH reduced P adsorption. However, at pH > 5, the P adsorption amount was maintained regardless of the pH increase. The presence of 10 mM SO42− and CO32− reduced P adsorption by 28.4% and 21.5%, respectively, and the impact of the presence of Cl− and NO3− was less than 10%. The feasibility of BA_CCM was tested using real wastewater, and 3.33 g/L of BA_CCM dose achieved a P removal ratio of 99.8% and a residual concentration of <0.02 mg/L. The toxicity unit of BA_CCM determined for Daphnia magna (D. magna) was 5.1; however, the BA_CCM after P adsorption (P-BA_CCM) did not show any toxicity to D. magna. BA_CCM after P adsorption was used as an alternative to commercial P fertilizer. Rice fertilized with a medium level of P-BA_CCM showed better agronomic values for most agronomic traits, except root length, than that seen with the commercial P fertilizer. This study suggests that BA_CCM can be used as a value-added product to address environmental issues.
Keywords: Adsorption mechanism; Bottom ash; Cattle manures; Daphnia magna; Energy; P fertilizers; P removal; Phosphorus recovery; Rice growths; Value added applications; Adsorption; Animals; Cattle; Coal Ash; Fertilizers; Hydroxyapatites; Manure; Oryza; Phosphorus; Soil; Wastewater; Adsorption mechanism; Fertilizer; Phosphorus; Rice growth; Toxicity; Wastewater